Rendahnya Pendidikan Di Nagari Koto Baru Kabupaten Padang Pariaman - Muhammad Refdinal; Hasrul Hasrul; Azwar Ananda (Journal of Civic Education, 2022)
This research is motivated by the low level of public education in the Koto Baru district and how the government responds in overcoming educational problems in the Koto Baru district. This study aims to describe: what are the factors causing the low level of public education in Nagari Koto Baru and how governments tackle this problems. This research is a qualitative descriptive study using data collection techniques by observation, interviews, and documentation studies. (3) The informants in this study were 4 upper class people, 6 lower class people, 4 teachers or educators, 1 Wali Nagari Koto Baru. The research results show that low level of education in village of Koto Baru caused by low level of parent’s education, bad transportations and lack of teacher. Based on this research, it is hoped that parents and the local government will always be able to motivate and supervise children in pursuing their education.